2018
DOI: 10.1186/s12284-018-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for the Role of a Rice Vacuolar Invertase as a Molecular Sink Strength Determinant

Abstract: BackgroundRice is a major crop feeding the majority of the global population, and increasing its sink strength is one of the modes to alleviate the declining availability of food for the rapidly growing world population. We demonstrate a role for an important rice vacuolar invertase isoform, OsINV3, in sink strength determination.ResultsOsINV3 mutants showed shorter panicles with lighter and smaller grains, owing to a smaller cell size on the outer and inner surfaces of the palea and lemma as observed by scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Invertases cleave sucrose into hexoses, which provide cells with fuel for respiration as well as with both carbon and energy for the synthesis of numerous different compounds (Goetz et al, ; Roitsch & Gonzalez, ). Furthermore, invertases are also involved in the long‐distance transport of sucrose by generating the necessary sucrose concentration gradient between phloem loading and unloading sites (Hu et al, ; Morey et al, ; Roitsch, Bittner, & Godt, ). This suggests that invertases are key metabolic enzymes involved in various aspects of the plant life cycle and the plant response to environmental stimuli (Chang et al, ; Naseem, Kunz, & Dandekar, ; Qin et al, ; Roitsch, Balibrea, Hofmann, Proels, & Sinha, ; Wang & Ruan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Invertases cleave sucrose into hexoses, which provide cells with fuel for respiration as well as with both carbon and energy for the synthesis of numerous different compounds (Goetz et al, ; Roitsch & Gonzalez, ). Furthermore, invertases are also involved in the long‐distance transport of sucrose by generating the necessary sucrose concentration gradient between phloem loading and unloading sites (Hu et al, ; Morey et al, ; Roitsch, Bittner, & Godt, ). This suggests that invertases are key metabolic enzymes involved in various aspects of the plant life cycle and the plant response to environmental stimuli (Chang et al, ; Naseem, Kunz, & Dandekar, ; Qin et al, ; Roitsch, Balibrea, Hofmann, Proels, & Sinha, ; Wang & Ruan, ).…”
Section: Introductionmentioning
confidence: 99%
“…5), suggesting that morphology-based phenotypic plasticity causing variation in C 501 source-sink ratio can affect TPU. A recent study also reported the effect of sink strength on 502 sucrose partitioning that may be used to increase grain yield in rice (Morey et al, 2018). More This study provided new insights into the effect of C source-sink relationships on rice 507 photosynthesis and in particular, its parameter TPU.…”
Section: Correlations Between Photosynthetic and Biochemical Parametementioning
confidence: 80%
“…The hexoses released by CWI or VI not only served as core metabolites and nutrient sources but also acted as key signaling molecules to impact on gene expression during developmental transitions and responding to environmental cues (Rolland et al, 2006;Ruan, 2014). The basic functions of VI in photoassimilate partitioning, cell expansion, and osmotic regulation have been implemented widely in a variety of plants (Klann et al, 1996;Kohorn et al, 2006;Sergeeva et al, 2006;Yu et al, 2008;Nägele et al, 2010;Morey et al, 2018). Suppression of VI activities showed a decrease of cold-induced sweetening (CIS), leading to improved processing qualities of potato tubers (Bhaskar et al, 2010;Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%